Closed abdominal trauma in polytrauma. Part II: surgical tactics for the damages control - S. I. Panasenko; S. O. Guriev; D. M. Lysun; V. A. Kushnir; R. V. Saliutin (Клінічна хірургія)
Closed abdominal trauma in polytrauma. Part II: surgical tactics for the damages control